Diversity of community relationships in community-based natural resource management - Lamug, Corazon B. (2008)
Community-based natural resource management (CBNRM) has gradually developed as a management paradigm representing a shift from a bureaucratic top-down approach to one that empowers communities to co-manage the resources that they utilize. The objective of the paper is to meta-analyze four categories of community relationships from different reports of studies on CBNRM. Ninety-five studies were reviewed and coded for meta-analysis of community relationships in the following categories: (1) Relationships of community with specific natural resource. The studies reflect two sets of beliefs: one is the interrelatedness of humans, nature and the supernatural; the other is belief in mastery of nature and utility of natural resources. (2) Relationships among community members. The themes are categorized into community attachment and cohesion, formal organization of community members and empowerment. (3) Relationships between community and non-government organizations (NGOs). The issues addressed in this category are organizational development, dependency-autonomy and networks. (4) Relationships between community and government agency/local government unit (GA/LGU). The themes are on policy and power relations, incentives and co-management. The paper concludes with the conceptual and methodological contributions of the study together with some implications of community relationships on natural resource management.
Keywords: Community Based Natural Resource Management